2009
DOI: 10.1038/ncb1920
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-derived CLASP-dependent microtubules control Golgi organization and polarized trafficking in motile cells

Abstract: Microtubules are indispensable for Golgi complex assembly and maintenance that is an integral part of cytoplasm organization in interphase mammalian cells. Here, we show that two discrete microtubule subsets drive two distinct, yet simultaneous, stages of Golgi assembly. In addition to the radial centrosomal microtubule array, which positions the Golgi in the cell center, we identify a role for microtubules that form at the Golgi membranes in a manner dependent on microtubule regulators CLASPs. These Golgi-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

27
363
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 268 publications
(393 citation statements)
references
References 44 publications
27
363
1
1
Order By: Relevance
“…Together with data from live imaging analyses 7 , these results have indicated that the formation of the Golgi ribbon proceeds in two distinct steps, in which the Golgi-derived MTs first draw the Golgi ministacks together in a tangential manner, whereas the centrosomal MTs subsequently drag the laterally clustered Golgi stacks towards the centrosome 7 . Interestingly, these studies have also demonstrated that loss of the Golgi ribbon resulted in unpolarized vesicle transport from the Golgi apparatus, and thereby impaired regulated lamellipodia development required for maintenance of directed cell migration 7,12 . Taken together, these studies have provided not only new insight into the importance of MTs in organelle architecture, but also evidence for the physiological significance of this vertebrate-specific Golgi architecture.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…Together with data from live imaging analyses 7 , these results have indicated that the formation of the Golgi ribbon proceeds in two distinct steps, in which the Golgi-derived MTs first draw the Golgi ministacks together in a tangential manner, whereas the centrosomal MTs subsequently drag the laterally clustered Golgi stacks towards the centrosome 7 . Interestingly, these studies have also demonstrated that loss of the Golgi ribbon resulted in unpolarized vesicle transport from the Golgi apparatus, and thereby impaired regulated lamellipodia development required for maintenance of directed cell migration 7,12 . Taken together, these studies have provided not only new insight into the importance of MTs in organelle architecture, but also evidence for the physiological significance of this vertebrate-specific Golgi architecture.…”
mentioning
confidence: 78%
“…However, the underlying mechanism for maintaining this specific Golgi arrangement as well as its physiological significance had been unclear until the above-mentioned studies. They have demonstrated that specific disruption of the Golgi-derived MTs by knockdown of CLASPs or AKAP450/CG-NAP converted the Golgi ribbon into a cluster of Golgi stacks gathering around the centrosome 7,9 . Together with data from live imaging analyses 7 , these results have indicated that the formation of the Golgi ribbon proceeds in two distinct steps, in which the Golgi-derived MTs first draw the Golgi ministacks together in a tangential manner, whereas the centrosomal MTs subsequently drag the laterally clustered Golgi stacks towards the centrosome 7 .…”
mentioning
confidence: 99%
See 3 more Smart Citations